Employability of Computer Science Graduates of President Ramon Magsaysay State University, Iba, Zambales from 2017-2021 - Pamplona, Carl Angelo S.; Sepillo, Geoffrey S.; Dela Cruz, Menchie A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study sought to determine the employment status of Bachelor of Science in Computer Science Graduates at President Ramon Magsaysay State University (PRMSU) Iba Zambales from 2017-2021. Additionally, it also analyzed the relevance of the graduate respondents' existing jobs and investigated the causes of their unemployment. The findings of this study will serve as a platform for future studies aimed at identifying the problems that graduates experience when looking for work, evaluating the performance of educators, and refining the Bachelor of Science in Computer Science curricula to align with the requirements of the industry 4.0 era. The researchers administered a survey to collect data on employment and job placement from the respondents. The results revealed that 46.48 percent of graduate respondents were presently employed in rank-and-file or clerical positions, while 36.62% held positions with professional, technical, and administrative roles directly related to their academic background. Additionally, 57.14 percent of unemployed graduate respondents cited their decision of not finding a job as the reason for being unemployed. The graduates were able to utilize the theoretical and technical proficiencies they learned throughout their academic training. It is highly recommended that further research be undertaken in future studies to enhance the study.